Associations between personality and musculoskeletal disorders in the general population: A systematic review protocol - Quirk, Shae E.; Koivumaa-Honkanen, Heli; Honkanen, Risto J.; Mohebbi, Mohammadreza; Kavanagh, Bianca E.; Heikkinen, Jeremi; Williams, Lana J. (Frontiers in Psychiatry, 2023)
There is growing evidence of the comorbidity between personality disorder (PD) and musculoskeletal disorders (MSDs). However, there are no systematic reviews including critical appraisal and meta-analyses that identify, evaluate, and synthesise the available evidence on these associations. Therefore, we present here a protocol of the methodology to undertake a systematic review, with the objective to evaluate associations between PD and MSDs in epidemiological population-based studies. A systematic review of observational studies will be conducted. A complete search strategy will be developed in consultation with a health librarian. To identify peer-reviewed literature, the search will be translated for, and implemented in Medline Complete, CINAHL Complete, and PsycINFO via the EBSCOhost platform from 1990–present. Grey literature will be identified using an adapted search in Google. Studies will be eligible if they examine general population participants aged 15 years and over. Associations of interest are the presence of threshold or positive screen according to the DSM-IV-5 (groupings: any, Clusters A, B, C, specific PD) or ICD-10 for PD in relation to arthritis, back/neck conditions, fibromyalgia, osteopenia/osteoporosis, and/or “any” of these MSDs. Data extraction and critical appraisal will be conducted in line with the Joanna Briggs Institute (JBI) guidance for systematic reviews of etiology and risk. The results from all studies will be presented in tables, text, and figures. A descriptive synthesis will present the characteristics of included studies, critical appraisal results, and descriptions of the main findings. Where appropriate, meta-analyses will be performed. If heterogeneity (e.g. I² =50%) is detected, subgroup/sensitivity analysis may be used to explore the possible sources. The systematic review does not require ethics approval. The proposed systematic review will strengthen the evidence base on what is known regarding associations between PD and MSDs by identifying, evaluating, and synthesising the findings of existing observational studies including meta-analyses, where appropriate.